Nano-Modified Asphalt Binders and Mixtures to Enhance Pavement Performance - Santos, Luís Picado; Crucho, João (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is dedicated to the use of nanomaterials for the modification of asphalt binders, and to investigate whether or not the use of nanomaterials for asphalt mixtures fabrication achieves more effective asphalt pavement layers. A total of 10 contributions are included. Four are related to "Binder's modification" and five to "Asphalt mixtures' modification". The remaining contribution is a review of the effects of the modifications on nanomaterials, particularly nanosilica, nanoclays and nanoiron, on the performance of asphalt mixtures. The published group of papers fosters awareness about the use of nanomaterials to modify asphalt mixtures to obtain more performant and durable flexible road pavements.